An Analysis Of The Students’ Difficulties In Reading Comprehension At SMA Negeri 13 Maluku Barat Daya - Dian Sartin Tiwery; Yulina Tiwery (Departement of Mathematics Education, 2024)
The purpose of this study is to analyze and describe students' difficulties in reading comprehension, causes of students’ difficulties, and the solution to overcome students’ difficulties in reading comprehension. This research used a qualitative descriptive method and this research used three instruments. They were questionnaire, observation, and interview. The research findings was some students’ difficulties in reading comprehension because they were misunderstanding the words, difficult to understand the long sentences, difficult to find the main idea, misunderstanding grammar, and difficulty in making conclusion. As a way to increase the students’ vocabularies, they have to learn the words, practice diligently, and learn to understand English reading. To help students become more proficient in reading comprehension, teachers must provide them with different reading practices.